2018
DOI: 10.1111/myc.12779
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of antifungal drugs against environmental Exophiala isolates and review of the literature

Abstract: Exophiala is a genus of black fungi isolated worldwide from environmental and clinical specimens. Data on antifungal susceptibility of Exophiala isolates are limited and the methodology on susceptibility testing is not yet standardised. In this study, we investigated in vitro antifungal susceptibilities of environmental Exophiala isolates. A total of 87 Exophiala isolated from dishwashers or railway ties were included. A CLSI M38-A2 microdilution method with modifications was used to determine antifungal susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…As shown in Table 2, bacterial orbital abscess develops within 4-6 weeks, whereas fungal [36,37]. The study of in vitro antifungal susceptibilities of environmental Exophiala isolates has shown that the most active antifungal agents are voriconazole and terbinafine, followed by posaconazole, itraconazole and amphotericin B, and that fluconazole has no meaningful antifungal activity against Exophiala [38]. In the current case, the recurrence of orbital abscess was observed without antifungal systemic treatment in the postoperative period of the first surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, bacterial orbital abscess develops within 4-6 weeks, whereas fungal [36,37]. The study of in vitro antifungal susceptibilities of environmental Exophiala isolates has shown that the most active antifungal agents are voriconazole and terbinafine, followed by posaconazole, itraconazole and amphotericin B, and that fluconazole has no meaningful antifungal activity against Exophiala [38]. In the current case, the recurrence of orbital abscess was observed without antifungal systemic treatment in the postoperative period of the first surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are no available standardized broth microdilution methodologies or validated MIC breakpoints for in vitro resistance testing for E. dermatitidis. However, numerous studies dealing with susceptibility patterns of the black yeast-like fungus exist [21,29,41,45,123,130,[132][133][134][135][136][137][138][139][140].…”
Section: Susceptibility and Resistancementioning
confidence: 99%
“…The antibiotic colistin which is also used for inhalation therapy in CF patients exhibited antifungal activity [148] and was able to reduce mature biofilm [130]. Future research in - [134][135][136][137] developing novel anti-infective agents for the treatment of E. dermatitidis infection is warranted. In CNS infections with E. dermatitidis, therapeutic studies suggest the complete excision of the brain abscess.…”
Section: Susceptibility and Resistancementioning
confidence: 99%
“…However, it is difficult to decide on the appropriate breakpoint for Candida species (24). In practice, voriconazole shows good results when administered at appropriate concentrations, according to therapeutic drug monitoring (25); the appropriate breakpoint for E. dermatitidis is still being investigated (26).…”
Section: Discussionmentioning
confidence: 99%